2018
DOI: 10.1080/00325899.2018.1437336
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for dynamic compaction of Mg–SiC nanocomposite powder using a modified Split Hopkinson Pressure Bar

Abstract: In this paper, fabrication and characterisation of Mg-SiC nanocomposite are investigated. Micrometre-sized Mg powder with the different volume fraction of SiC nano particles were dynamically compacted using a modified Split Hopkinson Pressure Bar. Moreover, the compaction process was simulated using AUTODYN commercial software to demonstrate that the stress in the powder sample was sufficient for consolidation. To achieve the best quality samples, the effects of lubrication and compaction velocity on dynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The first part of the investigation 14 dealt with production of the nanocomposite samples using DH testing device at different temperatures. The second part of the investigation 15 was related to fabrication of the nanocomposites using Hopkinson bar testing apparatus at a single temperature. The main objective of this work is to study the effect of compaction temperature on density, microhardness, and compaction behavior of samples produced by high-rate consolidation technique using a split Hopkinson pressure bar (SHPB).…”
Section: Introductionmentioning
confidence: 99%
“…The first part of the investigation 14 dealt with production of the nanocomposite samples using DH testing device at different temperatures. The second part of the investigation 15 was related to fabrication of the nanocomposites using Hopkinson bar testing apparatus at a single temperature. The main objective of this work is to study the effect of compaction temperature on density, microhardness, and compaction behavior of samples produced by high-rate consolidation technique using a split Hopkinson pressure bar (SHPB).…”
Section: Introductionmentioning
confidence: 99%
“…22 The compactions are performed using a die with sufficient rigidity. More details about design and material of the die can be found in Rahmani et al 10 All compaction processes were carried out at temperature of 450 C using a 1200 W ceramic heating element. This temperature is close to the sintering temperature of magnesium which is 0.75 of its melting point.…”
Section: Fabrication Proceduresmentioning
confidence: 99%
“…16 Sample's density was measured using the Archimedes principle. 10 In this study, the specimens fabricated under quasi-static loading are shown by QS, the samples produced using drop hammer are denoted by DH and the samples fabricated using Split Hopkinson bar are specified by SHB. The flowchart of the procedure of nano/microcomposite fabrication and test program is shown in Figure 3.…”
Section: Fabrication Proceduresmentioning
confidence: 99%
See 2 more Smart Citations